The effect of previous group interaction on individual ideation novelty and variety. Issue 1 (3rd April 2018) - Coelho, Denis A.; Vieira, Fátima Lanhoso
Abstract: The effect of antecedent group interaction on individual ideation is investigated, through an experiment based on generation of concepts by two groups of industrial design students following the same design brief. The underlying hypothesis is that preceding individual ideation with group interaction promotes increase in effectiveness of individual ideation. Results were analyzed for maximum novelty of individual ideation, showing a positive post-treatment effect, departing sharply from the novelty degradation in the control group in the second phase of the experiment. Analysis of the ideation outcomes using a variety metric, complement the findings obtained for novelty, in characterizing the effect of group interaction in creative ideation, demonstrating an inverse effect of previous group interaction leading to decreased variety of ideation.